2016
DOI: 10.1634/theoncologist.2015-0470
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Capecitabine/Temozolomide in Metastatic Neuroendocrine Tumors

Abstract: Background. Neuroendocrine tumors (NETs) are commonly treated with multimodality therapy. The combination of capecitabine and temozolomide (CAPTEM) has been suggested as a treatment option for patients with metastatic NETs. We present our experience with CAPTEM. Methods. Data on NET patients who were placed on CAPTEM and received at least one cycle were obtained from a Velos eResearch database. Response rate was calculated by RECIST 1.1. Overall survival and progression-free survival (PFS) were calculated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 23 publications
1
64
0
Order By: Relevance
“…Recently Ramirez et al[51] reported the results of another study reviewing the CAPTEM regimen again but in a wide variety of metastatic NETs. Twenty nine patients were included, small bowel (31%), pancreas (52%), lung (10%), and rectum (7%)[51].…”
Section: Chemotherapy: Past Present and Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently Ramirez et al[51] reported the results of another study reviewing the CAPTEM regimen again but in a wide variety of metastatic NETs. Twenty nine patients were included, small bowel (31%), pancreas (52%), lung (10%), and rectum (7%)[51].…”
Section: Chemotherapy: Past Present and Futurementioning
confidence: 99%
“…Twenty nine patients were included, small bowel (31%), pancreas (52%), lung (10%), and rectum (7%)[51]. …”
Section: Chemotherapy: Past Present and Futurementioning
confidence: 99%
“…In fact, regression and control of the tumor are highly needed and very important in patients with large symptomatic tumors [16][17][18][19]. In recent years, the CAPTEM regimen (capecitabine and temozolomide) has emerged with exceptionally promising objective RR and overall survival duration [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that continuous antimetabolite (capecitabine) treatment with a lipophilic methylator (temozolomide) may lead to better control of tumor growth and may be efficacious for NETs [13][14][15][16]. Considering that S-1 is also a fluoropyrimidine antimetabolite agent, we treated metastatic NETs with the STEM regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Even the alternative alkylating agent temozolomide, which has been explored clinically for treating NETs including in phase II trials, has resulted in limited therapeutic benefit in carcinoids specifically, as described in the above discussion 1317 . Clinical challenges surrounding temozolomide and similar cytotoxic drugs are reflected by a study by Ramirez et al who although endorse survival benefits from temozolomide and capecitabine therapy in metastatic NET patients, add that adverse reactions forced dose reductions in 24% of patients 66 . Therefore, translating these treatments into effective and rational therapeutic regimens is challenging, particularly due to the long natural histories of carcinoids making formal treatment comparisons difficult to devise.…”
Section: Discussionmentioning
confidence: 99%